1994
DOI: 10.1200/jco.1994.12.10.2071
|View full text |Cite
|
Sign up to set email alerts
|

First isolated locoregional recurrence following mastectomy for breast cancer: results of a phase III multicenter study comparing systemic treatment with observation after excision and radiation. Swiss Group for Clinical Cancer Research.

Abstract: Systemic therapy with TAM after isolated locoregional recurrence of breast cancer significantly increased 5-year DFS rates from 36% to 59% compared with observation alone and prolonged median DFS by more than 4.5 years in patients with ER+ tumors or in the case of unknown ER status with a DFI of greater than 12 months and minimal tumor burden. Treatment with TAM currently has no significant impact on OS, but the median survival duration of the study population has not yet been reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
101
1
8

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(113 citation statements)
references
References 24 publications
3
101
1
8
Order By: Relevance
“…However, this hypothesis was addressed in 167 patients with a first isolated local and regional recurrence after mastectomy for breast carcinoma in a Swiss Phase III multicenter study comparing tamoxifen with observation after local therapy. 63,64 Although a local recurrence of breast carcinoma after mastectomy appears to confer a worse prognosis in general than local recurrence after breast conservation, the results of this multicenter study have implications for the latter clinical scenario. 23,65,66 At a median follow-up of 11.6 years in surviving patients, tamoxifen was associated with improved disease-free survival (61% vs. 33%; P ϭ 0.006).…”
Section: Impact Of Systemic Therapy Given At the Time Of Inbreast Locmentioning
confidence: 91%
“…However, this hypothesis was addressed in 167 patients with a first isolated local and regional recurrence after mastectomy for breast carcinoma in a Swiss Phase III multicenter study comparing tamoxifen with observation after local therapy. 63,64 Although a local recurrence of breast carcinoma after mastectomy appears to confer a worse prognosis in general than local recurrence after breast conservation, the results of this multicenter study have implications for the latter clinical scenario. 23,65,66 At a median follow-up of 11.6 years in surviving patients, tamoxifen was associated with improved disease-free survival (61% vs. 33%; P ϭ 0.006).…”
Section: Impact Of Systemic Therapy Given At the Time Of Inbreast Locmentioning
confidence: 91%
“…30 Such beneficial effects have been demonstrated by tamoxifen use in patients with isolated LRR after mastectomy. 40 It has been demonstrated by several groups of authors that the method by which a local recurrence is detected is a predictor of outcome in patients with IBTR after BCT. 28,31 Patients who have local recurrences detected by mammography or by a combination of mammography and physical examination have a better prognosis than patients who have recurrences detected by physical examination alone.…”
mentioning
confidence: 99%
“…In case of a positive oestrogen and/or progesterone receptor status however, patients with local recurrence are candidates for hormonal treatment anyway, irrespective of their axillary nodal status. This decision is supported by results from a randomized controlled trial, which showed an increase of 5-year disease-free survival for patients with local recurrence treated with tamoxifen compared to observation alone (Borner 1994). 11 Until now, the effectiveness of chemotherapy in patients with local recurrence has remained unclear, 12,13 and a randomized study is ongoing to determine the value of chemotherapy in this setting.…”
Section: Reasons To Stage the Axillamentioning
confidence: 48%